Sosialisasi Fisioterapi Terhadap Pencegahan Postur Tubuh Yang Buruk Pada Siswa Di SDN Baros Mandiri 4 Kota Cimahi - Ika Rahman; April Vantulo Zalukhu; Audrey Reisana Aulia; Moch Fauzian (Insight Power (Kekuatan Wawasan), 2022)
Poor posture can be caused by several factors including frequent backpacks with too much weight and lack of ergonomics in standing, sitting, and lying, which can cause health problems such as waist, neck, and leg pain. This community service activity is socialization against the prevention of poor posture in students at SDN Baros Mandiri 4 Cimahi with 54 students in IVD and IVE class targets. The goal is to provide endurance training for prevention of poor posture in students. The result of this activity was 60% of the 54 students and students in grades IVD and IVE at SDN Baros Mandiri 4 Cimahi complained of dizziness, tingling, and soreness both on their neck, hands and feet after studying for approximately 1-2 hours because they sat too long in a hunchback, cradling their backpacks and playing cell phonesIn the sleeping position for 3-4 hours a day, As well as 10% of students and class IVD and IVE students experience shoulder and waist pain due to carrying too heavy a back bag and studying in a bent state with a long sitting position, resulting in waist pain.Keyword: Students, Body Posture